1984
DOI: 10.1007/bf00556895
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of a novel orally active angiotensin converting enzyme inhibitor (HOE 498) in healthy subjects

Abstract: The pharmacokinetics and pharmacodynamics of the angiotensin converting enzyme inhibitor HOE 498 were investigated in 10 healthy normotensive male subjects. Serum levels of the active metabolite M 1 (dicarboxylic acid) of HOE 498 were measured by HPLC up to 14 days after a single oral dose of 10 mg HOE 498. Peak serum concentration of M 1 between 5-50 ng/ml was observed 1.5-3.0 h after administration. The serum concentration-time curve of M 1 was polyphasic and exhibited a prolonged terminal phase with a half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 10 publications
6
18
0
Order By: Relevance
“…The biphasic pharmacokinetic profile of cilazaprilat observed in this group of hypertensive patients is qualitatively similar to that observed with other non-thiol containing ACE inhibitors (Ulm et al, 1982;Witte et al, 1984;Lees & Reid, 1987). The profile is consistent with high affinity saturable binding of cilazprilat to plasma ACE.…”
Section: Discussionsupporting
confidence: 81%
“…The biphasic pharmacokinetic profile of cilazaprilat observed in this group of hypertensive patients is qualitatively similar to that observed with other non-thiol containing ACE inhibitors (Ulm et al, 1982;Witte et al, 1984;Lees & Reid, 1987). The profile is consistent with high affinity saturable binding of cilazprilat to plasma ACE.…”
Section: Discussionsupporting
confidence: 81%
“…This study has confirmed the rapid absorption of ramipril and its conversion to the active metabolite ramiprilat after oral administration (Becker et al 1984;Witte et al 1984). The peak concentration of ramiprilat in plasma appeared about 2 hours following oral administration of ramipril.…”
Section: Discussionsupporting
confidence: 65%
“…An interval of at least 2 weeks separated study days. The long wash-out period was chosen because ramiprilat can still be detected more than a week after administration of a single dose of ramipril [20].…”
Section: Medication and Dosagementioning
confidence: 99%